The Dome Fuji ice core DF2021 chronology (0-207 kyr BP) - Oyabu, Ikumi; Kawamura, Kenji; Buizert, Christo; Parrenin, Frédéric; Orsi, Anais; Kitamura, Kyotaro; Aoki, Shuji; Nakazawa, Takakiyo (Quaternary Science Reviews, 2022)
International audience Precise ice-core chronologies are essential for identifying the timing and duration of polar climatic changes as well as their phasing with the changes in other parts of the globe. However, existing ice-core chronologies beyond the last 60 kyr show relatively large disagreements with each other and with U-Th chronologies of speleothems. Here, we constructed new ice and gas age scales for the Dome Fuji (DF) core (DF2021) over the last 207 kyr by combining a Bayesian dating model and firn densification model, constrained by various types of chronological and glaciological information including new δO 2 /N 2 age markers, precise synchronization to other high-quality chronologies (volcanic, cosmogenic, and CH 4 signals), and high-resolution δ 15 N of N 2 (reflecting past firn thickness). The new chronology is tightly constrained by synchronization to other well-dated records for the last 60 kyr, whereas it is independent from other chronologies for the older period. For the last 60 kyr, the DF2021 chronology agrees with the layer-counted ice core chronologies (GICC05 and a part of WD2014) and U-Th chronologies of speleothems within ∼200 years. For the period 60-130 kyr BP, the timing of all Dansgaard-Oeschger warming events on DF2021 agree with those of corresponding events in the U-Th dated Chinese or European speleothems mostly within 1 kyr (well within 2σ uncertainty of DF2021). The excellent agreement suggests high accuracy of our chronology, and supports the assumption of negligible phasing between the past local summer solstice insolation and δO 2 /N 2 fractionation at bubble close-off (the basis for constructing the δO 2 /N 2 age markers). Between 130 and 207 kyr BP (penultimate glacial period), there is a lower degree of similarity between the variations in atmospheric CH 4 and speleothem calcite δ 18 O than in the last glacial period, making the age comparison challenging. The comparison of DF2021 with 9 U-Th dates at 7 abrupt events shows the mean difference of -0.2 ± 0.8 kyr, ...